A Pilot, Prospective, Observational Study to Investigate the Value of NGS in Liquid Biopsies to Predict Tumor Response After Neoadjuvant Chemo-Radiotherapy in Patients With Locally Advanced Rectal Cancer: The LiBReCa Study - Roesel, Raffaello; Epistolio, Samantha; Molinari, Francesca; Saletti, Piercarlo; De Dosso, Sara; Valli, Mariacarla; Franzetti-Pellanda, Alessandra; Deantonio, Letizia; Biggiogero, Maira; Spina, Paolo; Popeskou, Sotirios Georgios; Cristaudi, Alessandra; et al. (Frontiers in Oncology, 2022)
Introduction Circulating tumor DNA (ctDNA) has been shown to correlate with response to therapy in different types of cancer. However, in patients with locally advanced rectal cancer (LARC) little is known on how ctDNA levels change with neoadjuvant chemoradiation (Na-ChRT) and how they correlate with treatment response. The aim of the present work was to explore the value of serial liquid biopsies to monitor response after Na-ChRT with the hypothesis that this could become a reliable biomarker to identify patients with complete response, candidates for non-operative management. Materials and Methods Twenty-five consecutive LARC patients undergoing long course Na-ChRT therapy were included. Applying next-generation sequencing (NGS), we characterized DNA extracted from formalin-fixed paraffin embedded diagnostic biopsy and resection tissue, and plasma ctDNA collected at the following time points: the first and last day of radiotherapy (T0, Tend), at 4 (T4), 7 (T7) weeks after radiotherapy, at the day of surgery (Top), and 3-7 days after surgery (Tpost-op). At the day of surgery a mesenteric vein sample was also collected (TIMV). The relationship between the ctDNA at those time-points and the Tumor Regression Grade (TRG) of the surgical specimen was statistically explored. Results We found no association between disappearance of ctDNA mutations in plasma samples and pathological complete response (TRG1) as ctDNA was undetectable in the majority of patients from Tend on. However, we observed that poor (TRG 4) response to Na-ChRT was significantly associated to a positive liquid biopsy at Top. Conclusions ctDNA evaluation by NGS technology may identify LARC patients with poor response to Na-ChRT. On the contrary, this technique does not seem to be useful to identify patients prone to develop a complete response. Keywords: Liquid Biopsy, ctDNA, Rectal Cancer, LARC, Watch and Wait approach, next-generation sequencing.